Imaging of the oral cavity and the oropharynx - SEMİZ OYSU, ASLIHAN (Springer Nature, 2023)
Imaging of the oral cavity and the oropharynx is essential for the diagnosis of neoplastic and nonneoplastic disease, assessment of the nature and extent of the lesion, detection of lymphadenopathy, design of the proper treatment, and follow-up after treatment. Approximately 90% of the tumors of the oropharynx and the oral cavity are squamous cell carcinomas. Diagnosis of mucosal lesions by clinical examination is usually straightforward; however deep extension of tumors should be assessed by computed tomography and/or magnetic resonance imaging. Imaging also helps clinicians find the primary tumor site in patients presenting with nodal metastases and detect submucosal lesions without mucosal abnormality.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE